Medicine Consumption Reminder and Monitoring Application for Patients with Leprosy Disease - Paulus Lucky Tirma Irawan; Calvin Brylland Septhanya Hartanto; Oesman Hendra Kelana (LPPM Universitas Ma Chung, 2022)
Leprosy or also known as Hansen's disease (HD) or Morbius Hansen's disease (MHD) caused by the bacterium Mycobacterium leprae. The symptoms of leprosy are hardly identified. In fact, some symptoms only can be identified after 20-30 years. Recently, the advent of multidrug therapy (MDT) and the use of anti-inflammatory therapies have given substantial improvements in long-term health outcomes for patients diagnosed with leprosy. However, the medication was a time consuming. Healthy behavior in the management of leprosy treatment requires discipline in taking leprosy medication. On the contrary, poor treatment management will lead to permantent consequnces of disability and deformity. Various Android-based applications have been developed by programmers. Smartphone technology is expected to help patients taking medication in supervising and reminding. In addition, through the cloud based technology the mobile application is expected to be solution as medium of information and communication for every stake holder in dealing with leprosy patients. This research involves a series of software development processes which are divided into several phases. Starting with the identification of the problem, moving on to the design of the application and the API service, to the development and testing of the application using a variety of test scenarios, and concluding with the documentation process. Both the functionality and the design were tested using the User Experience Questionnaire (UEQ) and black-box testing. Based on the outcomes of black box testing, the app's functionality work without any issues. The UEQ results show that novelty (Good), stimulation (Good), efficiency (Good), reliability (Above Average), perspicuity (Above Average), and beauty (Good) are all positive (Above Average). According to the UEQ results, the application received the highest efficiency level rating of 1.75, which indicates that it is regarded as having good consumption efficiency and being usable.